Transparent antibacterial nanofiber air filters with highly efficient moisture resistance for sustainable particulate matter capture - Liu, Hui (2020)
Particulate matter (PM) pollution has posed great threat to human health. This calls for versatile protection or treatment devices that are both efficient and easy to use. Herein, we have rationally designed a novel reusable bilayer fibrous filter consisting of electrospun superhydrophobic poly(methylmethacrylate)/polydimethylsiloxane fibers as the barrier for moisture ingression and superhydrophilic chitosan fibers for a PM capture efficiency of over 96% at optical transmittance of 86%. Furthermore, it could realize a high-level PM2.5 capture efficiency (>98.23%) even after 100-h test during extremely hazardous air environment (PM2.5 > 3,000 μg m−3) and retain a high PM removal efficiency (PM2.5 > 98.39%) after five washing cycles. Besides, such membranes possessed high antibacterial activity at 96.5% for E. coli and 95.2% for Staphylococcus aureus. As a proof-of-concept study, continuous particle removing has been successfully demonstrated on a window screen to prevent particle pollution.